Tokoh-tokoh Dalam Novel Love, Lost and Found (Cinta, Hilang dan Ditemukan) Karya Titi Sanaria: Kajian Psikologi Sastra - Sinabutar, Agnes Meylany; Wardiah, Dessy; Nazaruddin, Nazaruddin (ANTHOR: Education and Learning Journal, 2022)
Literary psychology is a science that examines literary works that are believed to reflect mental processes and activities. In examining psychological work, what needs to be understood is the extent of the author's psychological involvement and the author's ability to present figures who are involved with psychology. The problem in this research is how to classify the emotions of the characters in the novel Love, Lost, and Found by Titi Sanaria. The purpose of this research is to identify and describe the emotional classification of the characters in the novel Love, Lost and Found by Titi Sanaria. This research is a qualitative descriptive study. The data source for this research is the novel Love, Lost and Found by Titi Sanaria published by PT Elex Media Komputindo, published in 2019. The data collection techniques in this study were literature study, reading techniques, and note-taking techniques. The data validation technique in this study uses triangulation. The data analysis technique in this study used content analysis. The results of the research show that the novel Love, Lost and Found by Titi Sanaria, tells about a girl who likes to close herself off in this novel, there are 7 emotional classifications of the characters consisting of (1) the concept of guilt, (2) the feeling of guilt that is harbored, (3) self-punishment, (4) shame (5) sadness, (6) hatred, and (7) love.